2015
DOI: 10.1155/2015/154762
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CeramideDe NovoSynthesis Ameliorates Diet Induced Skeletal Muscles Insulin Resistance

Abstract: Nowadays wrong nutritional habits and lack of physical activity give a rich soil for the development of insulin resistance and obesity. Many researches indicate lipids, especially the one from the sphingolipids class, as the group of molecules heavily implicated in the progress of insulin resistance in skeletal muscle. Recently, scientists have focused their scrutiny on myriocin, a potent chemical compound that inhibits ceramide (i.e., central hub of sphingolipids signaling pathway) de novo synthesis. In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 33 publications
(42 reference statements)
5
44
1
Order By: Relevance
“…Our work presented here clearly demonstrates that genetic, pharmacological or dietary manipulation aimed at altering ceramide levels in the heart, likely acting via a number of CIPs, elicits cardiac defects associated with LCM. Inhibition of ceramide synthesis has been reported to have beneficial effects in several models related to metabolic syndrome and lipotoxicity, including obesity (Yang et al, 2009), diabetes and insulin resistance (Kurek et al, 2015; Ussher et al, 2010), non-alcoholic fatty liver disease (Kasumov et al, 2015; Kurek et al, 2015), and atherosclerotic plaques (Park et al, 2008b). …”
Section: Discussionmentioning
confidence: 99%
“…Our work presented here clearly demonstrates that genetic, pharmacological or dietary manipulation aimed at altering ceramide levels in the heart, likely acting via a number of CIPs, elicits cardiac defects associated with LCM. Inhibition of ceramide synthesis has been reported to have beneficial effects in several models related to metabolic syndrome and lipotoxicity, including obesity (Yang et al, 2009), diabetes and insulin resistance (Kurek et al, 2015; Ussher et al, 2010), non-alcoholic fatty liver disease (Kasumov et al, 2015; Kurek et al, 2015), and atherosclerotic plaques (Park et al, 2008b). …”
Section: Discussionmentioning
confidence: 99%
“…6C). Sphingolipids have been attributed to, among others, insulin resistance, inflammation, and carcinogenesis (71)(72)(73). Detection of high levels of sphingolipids in the serum of obese animals could indicate the potential for susceptibility to many diseases.…”
Section: Discussionmentioning
confidence: 99%
“…As lipids accumulate, the levels of the CER and DAG increase, which impairs the insulin signaling pathway and promotes insulin resistance [96]. Studies have shown that increased CER levels in skeletal muscle in older individuals can promote insulin resistance [14], while reducing CER and DAG synthesis can improve skeletal muscle insulin sensitivity [61].…”
Section: Intramyocellular Lipid Accumulation Can Increase the Risk Ofmentioning
confidence: 99%